Gendered transformations : theory and practices on gender and media - Krijnen, Tonny; Alvares, Claudia; Bauwel, Sofie van (European Communication Research and Education Association series., 2011)
"Comprising the most current scholarship from leading experts in the fields of gender and media studies, Gendered Transformations offers readers a new foundation from which to reexamine traditional perspectives on gender and media. Organized into sections concerning representational politics, embodied performance, and social constructions of reality, these essays explore a wide variety of concerns from a similarly wide variety of perspectives. As Liesbet van Zoonen states in the introduction to this volume: 'In the current cultural condition of multimediality and intertextuality it makes more sense ... [to] see how particular media and media combinations are articulated with [particular issues] in situated diachronic and synchronic contexts.' A thought-provoking contribution to a number of disparate fields, Gendered Transformations offers a rare interdisciplinary approach to gender that reflects the most recent developments in media theory and methodology."--Page 4 of cover